Jennifer chan is not alone eaudiobook - Keller, Tae (Listening Library, 2022)
In her first novel since winning the Newbery Medal for When You Trap a Tiger , Tae Keller offers a gripping and emotional story about friendship, bullying, and the possiblity that there's more in the universe than just us. Sometimes middle school can make you feel like you're totally alone in the universe...but what if we aren't alone at all? Thanks to her best friend, Reagan, Mallory Moss knows the rules of middle school. The most important one? You have to fit in to survive. But then Jennifer Chan moves in across the street, and that rule doesn’t seem to apply. Jennifer doesn’t care about the laws of middle school, or the laws of the universe. She believes in aliens—and she thinks she can find them. Then Jennifer goes missing. Using clues from Jennifer’s journals, Mallory goes searching. But the closer she gets, the more Mallory has to confront why Jennifer might have run . . . and face the truth within herself. Tae Keller lights up the sky with this insightful story about shifting friendships, right and wrong, and the power we all hold to influence and change one another. No one is ever truly alone.